2003
DOI: 10.1021/jo0268299
|View full text |Cite
|
Sign up to set email alerts
|

Facile Intramolecular Cyclization in Oxidative Coupling of Acetylenes Linked to 1,3-Positions of Benzene:  Strained [12]Metacyclophanedienetetrayne System

Abstract: Oxidative coupling of ethynylpropellane linked to 1,3,5-position of a benzene core 3b did not give the cage dimer 2 but the dimer 4 having a strained [12]metacyclophanedienetetrayne system. The spectral and structural features of the novel ring system were revealed for the simple dibenzo derivative 6, which was also prepared efficiently by the intramolecular cyclization of the open-chain precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…TBA salts, AgPF 6 and [Cu I (CH 3 -CN) 4 ](PF 6 ) were stored in a vacuum dessicator under reduced pressure. The precursors 5-t butyl-1,3-diiodobenzene (32) and 5-t butyl-1,3-diethynylbenzene (33,34) were synthesised in two and four steps, respectively, from 4-t butyl-aniline by slight modifications of literature procedures. All other compounds were bought commercially and used as received.…”
Section: General Remarksmentioning
confidence: 99%
“…TBA salts, AgPF 6 and [Cu I (CH 3 -CN) 4 ](PF 6 ) were stored in a vacuum dessicator under reduced pressure. The precursors 5-t butyl-1,3-diiodobenzene (32) and 5-t butyl-1,3-diethynylbenzene (33,34) were synthesised in two and four steps, respectively, from 4-t butyl-aniline by slight modifications of literature procedures. All other compounds were bought commercially and used as received.…”
Section: General Remarksmentioning
confidence: 99%
“…Our research group14a,b and others14c have previously observed that the termini separation of the reactive components for the cyclization of cyclophanes dictates whether the intra‐ or intermolecular product dominates. For alkynes, molecular modeling studies indicated that the intermolecular product is favored when the termini separation is greater than 7 Å.…”
Section: Methodsmentioning
confidence: 78%
“…Tobe et al discovered that tetrayne 315, a simplified model for a 3D C 48 precursor, furnishes intramolecular PDM 316, analogously to reactivity shown by the C 48 precursor (Scheme 8.67) [98].…”
Section: Mixed Pdmsmentioning
confidence: 97%